A diffuse interface model for cell blebbing including membrane-cortex coupling with linker dynamics - Werner, Philipp; Burger, Martin; Frank, Florian; Garcke, Harald (SIAM Journal on Applied Mathematics, 2022)
The aim of this paper is to develop suitable models for the phenomenon of cell blebbing, which allow for computational predictions of mechanical effects, including the crucial interaction of the cell membrane and the actin cortex. For this sake, we resort to a two-phase field model that uses diffuse descriptions of both the membrane and the cortex, which in particular allows for a suitable description of the interaction via linker protein densities. Besides the detailed modeling, we discuss some energetic aspects of the models and present a numerical scheme, which allows us to carry out several computational studies. In those, we demonstrate that several effects found in experiments can be reproduced, in particular, bleb formation by cortex rupture, which was not possible by previous models without the linker dynamics.<br